Epidemiology, oncologic results and risk stratifcation model for metachronous peritoneal metastases after surgery for pT4 colon cancers: results from an observational retrospective multicentre long¿term follow-up study - Estaire Gómez, Mercedes; Cerdán Santacruz, C.; Cano Valderrama, Ó.; Peña Ros, E.; Serrano del Moral, Á.; Pereira Pérez, F.; Flor Lorente, B.; Biondo, S. (My University, 2023)
Purpose Metachronous peritoneal metastases (MPM) following a curative surgery procedure for pT4 colon cancer is a chal lenging condition. Current epidemiological studies on this topic are scarce. Methods A retrospective multicentre trial was designed. All consecutive patients who underwent operations to treat pT4 cancers between 2015 and 2017 were reviewed. Demographic, clinical, operative, pathological and oncological follow-up variables were included. MPM were described as any oncological disease at the peritoneum, clearly diferent from a local recurrence. Univariate and multivariate Cox regression models were constructed. A risk stratifcation model was created on a cumulative factor basis. According to the calculated hazard ratio (HR), a scoring system was designed (HR<3, 1 point; HR>3, 2 points) and a scale from 0 to 6 was calculated for peritoneal disease-free rate (PDF-R). A risk stratifcation model was also created on the basis of these calculations. Results Fifty diferent hospitals were involved, which included a total of 1356 patients. Incidence of MPM was 13.6% at 50 months median follow-up. The strongest independent risk factors for MPM were positive pN stage [HR 3.72 (95% CI 2.56¿5.41; p<0.01) for stage III disease], tumour perforation [HR 1.91 (95% CI 1.26¿2.87; p<0.01)], mucinous or signet ring cell histology [HR 1.68 (95% CI 1.1¿2.58; p=0.02)], poorly diferentiated tumours [HR 1.54 (95% CI 1.1¿2.2; p=0.02)] and emergency surgery [HR 1.42 (95% CI 1.01¿2.01; p=0.049)]. In the absence of additional risk factors, pT4 tumours showed 98% and 96% PDF-R in 1-year and 5-year periods based on Kaplan¿Meier curves. Conclusions Cumulative MPM incidence was 13.6% at 5-year follow-up. The sole presence of a pT4 tumour resulted in high rates of PDF-R at 1-year and 5-year follow-up (98% and 96% respectively). Five additional risk factors diferent from pT4 status itself were identifed as possible MPM indicators during follow-up. Keywords Colon cancer · Metachronous peritoneal metastases · Second look · HIPEC · Risk stratifcation